QUEBRA DO TETO DE VIDRO: DESAFIOS DE ASCENSÃO DA MULHER NO CAMPO JURÍDICO. - Rocha, Marcelly Vitória Melo; Batista, Claudia Karina Ladeia; Silva, Maria Rita Nascimento da Silva (ANAIS DO ENIC, 2026)
.